NIILAI-NILAI TOLERANSI DALAM FILM AJARI AKU ISLAM DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Ilham Putri Handayani; Deni Irawan; Munawwar Khalil (Piwulang: Jurnal Pendidikan Agama Islam, 2021)
Currently, intolerant ideas are widely disseminated through social media, including one of them through on of them through the media, social media has a great influence on society. Dissemination of information through the world of film should be packaged with various positive values in it, including the values of tolerance. The study aims to analyze the values of tolerance in the film Ajari Aku Islam. The point of this research includes qualitative descriptive research with the source of the research being the DVD film Ajari Aku Islam directed by Deni Pusung, output 17 October 2019 bag and other supporting sourches. For the data analysis techniques used in this study consisted of data reduction, data presentation and drawing conclusions. The results of study indicate that: 1) the values of tolerance in the film Ajari Aku Islam include: a) respect and existence in religion, b) mutual understanding, c) agree and disagremant. 2) the relevance of tolerance values in the film Ajari Aku Islam include: a) in accordance with the objectives of Islamic religious education, b) Islamic religious education materials in the film AJari Aku Islam include Islamic faith, morals and Islamic law, c) and methods of Islamic religious education the methods of Islamic religious education the method used in this film is the exemplary method and discussion method.